2020
DOI: 10.1097/pcc.0000000000002385
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm Atrophy During Pediatric Acute Respiratory Failure Is Associated With Prolonged Noninvasive Ventilation Requirement Following Extubation

Abstract: Objectives: Diaphragm atrophy is evident during invasive ventilation for pediatric acute respiratory failure, but with unknown significance. We hypothesized that diaphragm atrophy in pediatric acute respiratory failure is associated with prolonged noninvasive positive pressure ventilation following extubation. Design: Prospective observational study. Setting: Single-center academic PICU. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 18 publications
1
36
1
1
Order By: Relevance
“…Prolonging the duration of mechanical ventilation causes many challenging complications, such as ventilator-associated pneumonia (VAP), pulmonary hemorrhage, tracheal injury, diaphragm atrophy, neuromuscular disorders, an increased length of ICU stay and an unfavorable discharge destination (5)(6)(7)(8). Moreover, there are no specialized weaning units for patients requiring PMV.…”
Section: Introductionmentioning
confidence: 99%
“…Prolonging the duration of mechanical ventilation causes many challenging complications, such as ventilator-associated pneumonia (VAP), pulmonary hemorrhage, tracheal injury, diaphragm atrophy, neuromuscular disorders, an increased length of ICU stay and an unfavorable discharge destination (5)(6)(7)(8). Moreover, there are no specialized weaning units for patients requiring PMV.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound determined diaphragmatic thickness and thickening fraction has shown that diaphragmatic atrophy is greater in patients on neuromuscular blockade and that diaphragmatic contractility was linearly correlated with patients' degree of spontaneous breathing ( 72 , 74 ). Ultrasound determined diaphragmatic atrophy has also been proven to be associated with prolonged post-extubation non-invasive positive pressure ventilation ( 73 ). These studies demonstrate the utility of diaphragmatic ultrasound as a tool to help identify patients who are at risk for diaphragmatic dysfunction-mediated morbidity.…”
Section: Current State Of Critical Care Point-of-care Ultrasoundmentioning
confidence: 99%
“…Diaphragmatic dysfunction is a loss of the muscular force generation of the diaphragm that has been associated with longer duration of mechanical ventilation and extubation failure (71)(72)(73). Ultrasound determined diaphragmatic thickness and thickening fraction has shown that diaphragmatic atrophy is greater in patients on neuromuscular blockade and that diaphragmatic contractility was linearly correlated with patients' degree of spontaneous breathing (72,74).…”
Section: Diaphragm Ultrasoundmentioning
confidence: 99%
“…Histologic evaluation has demonstrated diaphragm atrophy in adults who had 18‐69 h of diaphragmatic inactivity while on MV, with a decrease in size of both slow‐twitch and fast‐twitch muscle fibers 16 . The effect of diaphragm atrophy and dysfunction must not be underestimated as it has been associated with prolonged MV and increased complications in both adults and children 47,48 . In a single‐center study involving 31 children, significant diaphragm atrophy was noted in the first 24–48 h of MV, with substantial reductions in DTF and DT 30 .…”
Section: Assessment Of Atrophymentioning
confidence: 99%